Rasch analysis of the Katz index of independence in activities of daily living in senior citizens from Antioquia, Colombia - Diego Fernando Rojas-Gualdrón; Jessica María Ayala-Hernández; Doris Cardona-Arango; Angela María Segura-Cardona; María Osley Garzón-Duque (Universidad de Antioquia, 2019)
Improving Katz index interpretability contributes to a better understanding of its results facilitating decision making and intervention planning. Objective: To evaluate the validity of the Katz geriatric scale in senior citizens from a Rasch model perspective. Methodology: Secondary data analysis of a population-based, cross-sectional study of health status in 4,023 senior citizens conducted in Antioquia, Colombia, in 2012. Item fit, differential item functioning, unidimensionality, reliability and item-person map analyses were performed. Results: All items adjusted to the model. Transferring and Continence showed high differential item functioning with a considerable, but statistically non-significant impact on the overall estimation. Person and Item reliability were 0.80 and 0.90 respectively. The Rasch measurement explained 61.6% of variance. Conclusion: A unidimensional interval level measure can be obtained from the Katz instrument. It is important to do more research on differential functioning of Katz's items in a way in which validity arguments on its generalization to various subpopulations could be strengthened and score interpretability could be improved.